Deep learning : a visual approach - Glassner, Andrew S. (No Starch Press, Inc., 2021)
"A practical, thorough introduction to deep learning, without the usage of advanced math or programming. Covers topics such as image classification, text generation, and the machine learning techniques that are the basis of modern AI"--